2020
DOI: 10.3390/su12114753
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Corporate Sustainability Issues by Analyzing Shareholder Resolutions: A Machine-Learning Text Analytics Approach

Abstract: Corporations have embraced the idea of corporate environmental, social, and governance (ESG) under the general framework of sustainability. Studies have measured and analyzed the impact of internal sustainability efforts on the performance of individual companies, policies, and projects. This exploratory study attempts to extract useful insight from shareholder sustainability resolutions using machine learning-based text analytics. Prior research has studied corporate sustainability disclosures from public rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 98 publications
0
16
0
Order By: Relevance
“…We have also reviewed the studies on ESG solutions, another prominent subset of climate ntech that aids in sustainability investing. Increased demand for corporate sustainability has motivated companies to incorporate ESG considerations, communicated through shareholder resolutions and annual reports (Raghupathi et al, 2020). Tech-enabled ESG ratings are driving the market but are yet to attract academic interest (Hughes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We have also reviewed the studies on ESG solutions, another prominent subset of climate ntech that aids in sustainability investing. Increased demand for corporate sustainability has motivated companies to incorporate ESG considerations, communicated through shareholder resolutions and annual reports (Raghupathi et al, 2020). Tech-enabled ESG ratings are driving the market but are yet to attract academic interest (Hughes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most impact investors are the youth, millennials, Gen Z, and commercial and philanthropic investors (Weber, 2012;Schrötgens & Boenigk, 2017). Our literature reading on ESG points out that the increased demand for corporate sustainability has motivated companies to incorporate ESG considerations, communicated through shareholder resolutions and annual reports (Raghupathi et al, 2020). Hughes et al (2021) found tech-enabled ESG ratings leading the market but are yet to attract academic interest.…”
Section: Methodsmentioning
confidence: 98%
“…For example, Te Liew et al (2014) used the term frequency-inverse document frequency (TF-IDF) methodology to analyze more than 100 companies. Recently, studies have applied the LDA model: Ning et al (2021) analyzed 680 company disclosure data, and Raghupathi et al (2020) derived automated results (topics) through 1,737 more reports.…”
Section: Literature Reviewmentioning
confidence: 99%